1982
DOI: 10.1073/pnas.79.18.5587
|View full text |Cite
|
Sign up to set email alerts
|

Optic cup formation: a calcium-regulated process.

Abstract: Invagination of the optic vesicle to form the optic cup is an important event in the formation of the eye in the early embryo. To obtain support for earlier conclusions that a contractile process is involved, calcium dependency ofoptic cup formation was tested. Heads were excised from chicken embryos at the optic vesicle stage of development (stage 13) and incubated in nutrient medium containing antagonists or agonists of calcium transport. Invagination was reversibly inhibited by the Ca2+ antagonists verapami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…This interpretation is further supported by the finding that none of 48 stage 11-13 + embryos exhibited reopening of the occluded neurocoels when treated for 4 h r in medium 199 with agents known to mobilize intracellular Ca2+: 10 mM caffeine or theophylline. The concentration of these two drugs was identical to that used by Brady and Hilfer (1982) to show that in chick embryos of stages similar to those used in our study, optic cup morphogenesis was not reversed by 10 mM caffeine or theophylline.…”
Section: Pharmacological Reversal Of Spinal Cord Occlusionsupporting
confidence: 60%
See 2 more Smart Citations
“…This interpretation is further supported by the finding that none of 48 stage 11-13 + embryos exhibited reopening of the occluded neurocoels when treated for 4 h r in medium 199 with agents known to mobilize intracellular Ca2+: 10 mM caffeine or theophylline. The concentration of these two drugs was identical to that used by Brady and Hilfer (1982) to show that in chick embryos of stages similar to those used in our study, optic cup morphogenesis was not reversed by 10 mM caffeine or theophylline.…”
Section: Pharmacological Reversal Of Spinal Cord Occlusionsupporting
confidence: 60%
“…To determine whether occlusion requires calmodulin, embryos with occluded neurocoels were treated with three pharmacological agents known to be antagonists of calmodulin: chlorpromazine (CPZ) (Brady and Hilfer, 1982;Levin and Weiss, 1979), trifluperazine (TFP) (Levin and Weiss, 19771, and N-(6-aminohexyl)-5-chloro-1-napthalenesulfonamide (W-7) (Hidaka et al, 1981). The rationale for these treatments was based on the prevailing cell biology theory that all calmodulin reactions require Ca2' (Cheung, 1980).…”
Section: This Brings Up the Interesting Question Of How Ca2mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that the cellular cytoskeleton plays a role in the folding of numerous embryonal epithelial primordia (Hilfer and Searls 1986), and changes in the organisation of actin and myosin could bring about constriction of cell apices, inducing epithelial invagination. In this regard experimental manipulation of ATP levels or disruption in the transport of Ca ++ , conditions that interfere with the interaction of cytoskeletal actin and myosin, have been shown to disrupt invagination of the thyroid placode (Hilfer et al 1977), optic vesicle (Brady and Hilfer 1982), nasal placode (Smuts 1981) and neural plate (Lee et al 1983;Schoenwolf et al 1988;Ferreira and Hilfer 1993). Nevertheless, these manipulations apparently have no effect on invagination of the otic placode (Hilfer et al 1989), which indicates that the factors in question do not play a decisive role in the epithelial folds leading to otic vesicle formation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that this mechanism operates during the invagination of different ectodermic placodes such as the lens itself, the otic and nasal placodes and the neural tube, among others (Wrenn and Wessells, 1969;Bancroft and Bellairs, 1977;Brady and Hilfer, 1982;Ferreira and Hilfer, 1993); (2) a high rate of cell replication in the lens placode, with respect to the surrounding surface ectoderm, has been proposed as the mechanism responsible for creating forces involved in lens placode invagination (Modak, Morris and Yamada, 1968;Harding et al, 1971;Hendrix and Zwaan, 1974;A Â lvarez and Navascues, 1990;Hendrix, Madras and Johnson, 1993); (3) certain extracellular factors and, more speci®cally, extracellular matrix molecules, appear to be associated with epithelial invagination. What is more, it is known that alteration of the synthesis or enzyme degrading of particular matrix molecules such as collagen, certain proteoglycans and glycoproteins, may disrupt epithelial folding, as occurs in the branching of the salivary gland, lung and kidney primordia (Spooner and Faubion, 1980;Thompson and Spooner, 1983;Spooner, Bassett and Stokes, 1985;Nakanishi et al, 1986;Klein et al, 1989).…”
Section: Introductionmentioning
confidence: 99%